Differential effects of transcranial direct current stimulation on sprint and endurance cycling - Sasada, S.; Endoh, T.; Ishii, T.; Kawashima, K.; Sato, S.; Hayashi, A.; Komiyama, T. (Translational Sports Medicine, 2020)
Among well-trained athletes and across comparable experimental conditions, we investigated whether transcranial direct current stimulation (tDCS) (2 mA, 15 minutes) applied to the leg area of the motor cortex improved different cycling modes, namely, short sprint cycling and middle endurance cycling. Three different tDCS conditions, namely anodal, cathodal, and sham, were tested. Following tDCS, participants performed maximum effort sprint cycling for 8 seconds and sub-maximum power endurance cycling at a constant speed cadence until exhaustion. In the endurance test, time to exhaustion after anodal tDCS (715 ± 225 seconds) was significantly longer compared with after cathodal (670 ± 230 seconds) or sham tDCS (682 ± 216 seconds) conditions. Improvements in cycling performance due to anodal tDCS were observed in the endurance test with higher intensity cycling, with time to exhaustion approximately between 100 and 200 seconds. Neither anodal nor cathodal tDCS resulted in higher accumulative power output compared with sham tDCS in the sprint cycling test. Our findings suggest the effect of anodal tDCS over the motor leg area on cycling performance is strongly dependent on the differential development of central fatigue generated in different cycling modes. These findings aid understanding of the effects of tDCS on different cycling modes.